From Melanocyte to Metastatic Malignant Melanoma - Bizhan Bandarchi; Linglei Ma; Roya Navab; Arun Seth; Golnar Rasty (Hindawi Limited, 2010)
Malignant melanoma is one of the most aggressive malignancies in human and is responsible for almost 60% of lethal skin tumors. Its incidence has been increasing in white population in the past two decades. There is a complex interaction of environmental (exogenous) and endogenous, including genetic, risk factors in developing malignant melanoma. 8-12% of familial melanomas occur in a familial setting related to mutation of the CDKN2A gene that encodes p16. The aim of this is to briefly review the microanatomy and physiology of the melanocytes, epidemiology, risk factors, clinical presentation, historical classification and histopathology and, more in details, the most recent discoveries in biology and genetics of malignant melanoma. At the end, the final version of 2009 AJCC malignant melanoma staging and classification is presented.